2011
DOI: 10.1097/ta.0b013e3182307146
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Acute Care Surgery to Departmental Productivity

Abstract: The ACS practice model significantly enhances provider productivity and job satisfaction when compared with trauma alone. Fears of a productivity impact to the nontrauma general surgeon were not realized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…The main stimulus for ACS was mainly for the management of trauma in tertiary hospitals. Trauma management has increasingly become a non‐operative and underfunded area of surgery in the USA . In the USA, ACS remains a separate subspecialty with a dedicated fellowship programme …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main stimulus for ACS was mainly for the management of trauma in tertiary hospitals. Trauma management has increasingly become a non‐operative and underfunded area of surgery in the USA . In the USA, ACS remains a separate subspecialty with a dedicated fellowship programme …”
Section: Introductionmentioning
confidence: 99%
“…Trauma management has increasingly become a non-operative and underfunded area of surgery in the USA. 6 In the USA, ACS remains a separate subspecialty with a dedicated fellowship programme. 7 In Australia, the drive towards ASU was due to the increasing demand for EGS in public hospitals which was inadequately managed by the traditional on-call system.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these benefits include a reduction in time to consultation in the emergency department for nontrauma patients (5) and improved relativevalue unit productivity of emergency surgeons (6)(7)(8), including actual operative volume (9). Some of these benefits include a reduction in time to consultation in the emergency department for nontrauma patients (5) and improved relativevalue unit productivity of emergency surgeons (6)(7)(8), including actual operative volume (9).…”
mentioning
confidence: 99%
“…As ACS continues to flourish around the world, an increasing number of studies have emphasized the benefits of this care model for patients with general surgical emergencies [2,5,8,15-18]. Surgical departments, however, have historically been expensive to run because of the costly equipment, support staff, as well as the specialized nursing and medical staff required [19].…”
Section: Discussionmentioning
confidence: 99%
“…Miller et al [27] and Barnes et al [15] observed a 23% and 44% increase in operative productivity in terms of elective caseloads, respectively, but an overall decline in general surgery operative volumes because of a reduction in emergent cases [15]. However, neither study considered wait-times for elective cases.…”
Section: Discussionmentioning
confidence: 99%